Transforming Work : Early Modern Pastoral and Late Medieval Poetry - Little, Katherine C., 1969- (Book collections on Project MUSE., 2013)
Pastoral poetry has long been considered a signature Renaissance mode: originating in late sixteenth-century England via a rediscovery of classical texts, it is concerned with self-fashioning and celebrating the court. But, as the author demonstrates in this book, the pastoral mode is in fact indebted to medieval representations of rural labor. The author offers a literary history for the pastoral, arguing that the authors of the first English pastorals used rural laborers familiar from medieval texts -- plowmen and shepherds -- to reflect on the social, economic, and religious disruptions of the sixteenth century.